Managing Structure Related Risks For Highway Tunnelling Project In Malaysia A Contingency Plan For Menora Tunnel - Kamaruzaman, Nur Aini (Universiti Sains Malaysia, 2018)
Nowadays, tunnel is widely constructed and being utilised as an infrastructure due of their potential applications and their unique characteristics. Generally, tunnelling and underground structure works are usually easy to be exposed to possible risks especially in terms of the tunnel structure itself. These kinds of infrastructure have numerous tunnel related risks that need to be identified in order to improve the operation and maintenance for tunnelling project according to their potential risks. Therefore, the aim of this study is to identify the potential tunnel structure related risks and their priority-importance ranking towards successful delivery of highway tunnelling projects in term of operation and maintenance. The tunnel structure related risks for this research has been gathered from pilot study based on case study. Furthermore, an extensive interviews were conducted with a number of key personnel who involved in operation and maintenance stage for selected case study project in Menora Tunnel including OPUS and PLUS in order to obtain further information and justification for the identified risk. Thus, the results of these interview were used to determine their risk ranking through Analytical Hierarchy Process (AHP) analysis. Based on the results gathered from AHP analysis, the top three (3) listed risk on top can be categorized as predominant risk factors which are tunnel structure failure, contingency maintenance works due to tunnel risk, and cost overrun in operation due to tunnel risk. Thus, by identifying potential risk and be ranked accordingly to its prioritize, it will eventually facilitate the operator and authorities that in charge further revise the operation procedure and maintenance plan by including all this information. As a result, the current risk management plan in tunnelling projects can enhance the operation and maintenance of tunnelling projects in present and future by tackling unforeseen tunnel structure related risks.